Everyday econometricians: Selection neglect and overoptimism when learning from others - Kai Barron; Steffen Huck; Philippe Jehiel (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2019)
In this paper, we design an investment game which allows us to study the influence of selection when learning from others. Using the theoretical study of selection neglect in Jehiel (2018) as a guide, we test (i) for the presence of selection neglect in this investment context, and (ii) some comparative static predictions of the model. We find strong evidence for selection neglect—even though subjects are fully informed about the data generating process. As theoretically predicted, the degree of bias due to selection neglect increases when other decision makers become more informed, or become more rational. It decreases when signals are correlated.
Keywords: C11; C90; D80; D83; 330; selection neglect; beliefs; overconfidence; experiment; survivorship bias; bounded rationality